The kyai’s voice and the Arabic Qur’an; Translation, orality, and print in modern Java - Pink, Johanna (UI Scholars Hub, 2020)
This paper discusses practices of translating the Qur’an into Javanese in the Indonesian post-independence era. Focusing on works that emerged in pedagogical contexts, it demonstrates that the range of translation practices goes far beyond contemporary notions of scriptural translation. I argue that this is due to the oral origin of these practices and to the functions they assume in teaching contexts. These result in a higher visibility of the translator who appears as a religious authority in his1 own right. His voice might therefore be considered a valuable contribution to the translation, rather than a distortion of the source text’s true meaning. These dynamics are tied to the status of Javanese in a country in which the predominant language of print is Indonesian. Studying translation activities in languages without official status in the nation-state period contributes to widening our perspective on contemporary translation practices.